Finite Element Analysis for Bearing Capacity of Rectangular Footing Resting Near Sloped Cohesive soil - Jawdat K. Abbas (Tikrit Journal of Engineering Sciences, 2013)
Finite element method is used to investigate the ultimate bearing capacity of rectangular footing resting on cohesive soil near slope. The effect of footing aspect ratio (L/B), distance ratio (b/B), and slope angle (β) on the bearing capacity are calculated. A new reduction factor (Rs) is proposed to compute the ultimate bearing capacity for rectangular footing adjacent to slope of cohesive soil from ultimate bearing capacity for similar rectangular footing resting on ground level of cohesive soils. This study shows that the ultimate bearing capacity for rectangular footing adjacent to slope of cohesive soils decreases when slope angle (β) and aspect ratio (L/B) increases.  Also the ultimate bearing capacity increases when the distance ratio (b/B) increases. Finally The effect of slope diminishes as the distance ratio (b/B) equal, or exceeds 0.75.